Analysis of Heavy Metal Content and Magnetic Mineral Morphology in River Sediments in Bajuin District, South Kalimantan - Syahdiannor Syahdiannor; Sudarningsih Sudarningsih; Tetti Novalina Manik; I Kadek Febry Anggi Pangestu; Gerald Tamuntu (Lambung Mangkurat University Press, 2026)
Bajuin District is a sub-district located in Tanah Laut Regency, South Kalimantan, where there is gold mining around the river basin. Gold mining activities are often a source of pollution, especially heavy metals, to the aquatic environment. This study aims to determine the content of heavy metals and the morphological characteristics of magnetic minerals in river sediments in the gold mining area. Heavy metal content measurement was carried out using X-Ray Fluorescence (XRF) instruments and magnetic mineral morphology was carried out using Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS) instruments. The results of measurements using XRF in river sediments found heavy metals Fe (2,495.40 – 4,395.83), Mn (51.40 – 70.60), Cr (18.60 – 107.93), Ni (8.03 – 21.87), V (9.33 – 12.77), Cu (5.53 – 13.50), and Zn (4.60 – 6.33) in ppm units. The results of magnetic mineral measurements based on SEM show that magnetic minerals are octahedral and irregular. Meanwhile, the results of EDS measurements show that the main constituent elements of magnetic minerals are Fe and O which indicate magnetic minerals. In addition, elements Al, Si, Sc, V, Cr, Zn, Au, and Hg were also found. The results of this study provide important implications for environmental conditions in Bajuin District, especially related to the potential for increased heavy metal pollution due to gold mining activities around the river.